2012
DOI: 10.4314/ahs.v12i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the burden of human African trypanosomiasis by rapid participatory appraisal in three high-risk villages in Urambo District, Northwest Tanzania

Abstract: Background: The public health and socio-economic burden of Human African Trypanosomiasis (HAT) in East Africa is not well documented. Understanding the epidemiology and impact of HAT in such settings is difficult due to a lack of robust surveillance and reporting systems, restricting evidence-based policy development and contributing to the continued neglect of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Livestock production is the livelihood of the communities in two districts. Proportional piling showed that the cattle population scored the highest followed by goats and sheep with the median score of 32(14-40), 26 , and 21 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), respectively, as shown in Table 2. Donkey population is significantly high in Gnangatom communities than in Benna communities.…”
Section: Community Perceptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Livestock production is the livelihood of the communities in two districts. Proportional piling showed that the cattle population scored the highest followed by goats and sheep with the median score of 32(14-40), 26 , and 21 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), respectively, as shown in Table 2. Donkey population is significantly high in Gnangatom communities than in Benna communities.…”
Section: Community Perceptionmentioning
confidence: 98%
“…According to the two districts community informants, major cattle disease that affects animals in the area ranked in Table 3. Trypanosomosis and contagious bovine pleuropneumonia were ranked as first and second, with proportional median score of 24 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and 23 (19)(20)(21)(22)(23)(24)(25)(26), accordingly. In both two communities unanimously mentioned that the effect of trypanosomosis is very severe because of its negative socioeconomic impact.…”
Section: Major Cattle Diseasesmentioning
confidence: 99%
“…Health seeking behaviour studies have shown that HAT patients visit numerous public and private health providers over several months before being correctly diagnosed and treated [ 13 , 19 , 20 ]. Recovery periods typically take many months and HAT is thought to lead to many long-term disabilities caused by drug toxicity and infection, although the associated morbidity has not been quantified [ 21 ]. The DALY is not the only methodology that can be applied to quantify disease burden; economic calculations are also regularly used at both societal and household level – for example, impact of treatment costs and losses in income to patient households [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the data illustrated in Figure 1 are likely an underestimate. Many r-HAT foci are in remote areas; a lack of diagnostic facilities and awareness of HAT are frequently reported around foci [8,9] and underdetection of cases is a recognised problem [10]. Small numbers of cases are also regularly diagnosed in nonendemic countries, serving to highlight transmission that may not be reliably detected [11].…”
Section: Trendsmentioning
confidence: 96%